Vitamin E responsive neurological signs in ostriches (Struthio camelus). - Vasconcelos Meireles, Marcelo; Castendo Simoes, Daniel; Godik Antunes, Romulo; Machado, Gisele Fabrino [UNESP]; Savoya da Silva, Valeria Maria (My University, 2008)
Encephalomalacia in birds is commonly related to vitamin E deficiency. To the best of our knowledge, in ostriches there are no reports of neurological signs associated to nutritional deficiencies. Fourteen ostriches aged from 1 day to 3 weeks old were sent to necropsy and showed apathy, progressive weight loss, twisting or S-shaped flexure of the neck and mortality. Gross changes were mild and consisted of congested blood vessels besides edematous aspect of the cerebrum and cerebellum. Microscopic examination revealed congested meningeal vessels. Capillaries were evident in cortex and white matter of the encephalon. Focal spongy vacuolation and reactive gliosis were observed within the white matter of cerebellum. Four birds that presented neurological signs were inoculated by the subcutaneous route in the neck with 50 mg of vitamin E (alfatocoferol acetate), followed by clinical evaluation. These birds were fully recovered in a period of 24 h. Macroscopic and microscopic lesions associated to the clinical signs and to the therapeutic improvement provided by vitamin E administration are strong evidences of nutritional encephalomalacia (vitamin E deficiency).